Análisis de rentabilidad de las ventas en el Comercial Franklin ubicado en la ciudad de Babahoyo durante los meses de enero a junio del 2020 - Buruhan Santillan, Angela Andreina (2020)
The present work aims to detect the direct effects that influence the profitability of the sales of the “commercial Franklin” located in the city of Babahoyo, taking as a reference the context of the covid-19 pandemic and how it affected this company . The topics discussed revolved around the situation of the confinement itself that stopped the marketing and sale of the merchandise and therefore it was necessary to carry out the present study. For the development of this work, the necessary information was sought within the company for the application of different financial indices that allow us to know the financial position of the company. On the other hand, we also worked with the semiannual income statements that the company provided us to carry out our study and achieve the expected goal. The result allowed obtaining data through the application of financial methods, vertical analysis and horizontal analysis that helped us to determine that if there were significant variations within the main activity of the commercial, finally the objective was achieved and the respective analysis was carried out. The same that will help the company make decisions to apply strategies that help the salesperson to regain profitability in sales.